The Report "A Synodal Church in Mission" : An Orthodox View on the Implications for Orthodox-Catholic Unity - Miltos, Amphilochios Thomas (Proche-Orient chrétien, 2024)
The Synthesis Report of the First Session of the Assembly of the Synod of Bishops (Rome, October 2023) "A Synodal Church on Mission" is extremely interesting for the Orthodox, as it is linked to the issue of primacy, undoubtedly a major obstacle on the path to unity. This very brief presentation offers a reading of the report from an Orthodox perspective. Since it is difficult to examine such a long text, it focuses only on three issues: a) the participation of lay members in a Synod; b) the meaning of the idea of "all, some, one," and c) the relationship between primacy and synodality. By highlighting the Convergences, Questions to Consider, and Propositions on these three topics, this article attempts to contribute to the Catholic journey with and toward synodality.